Comparison of the validity, perceived usefulness and usability of I-MeDeSA and TEMAS, two tools to evaluate alert system usability: a study protocol - Melissa T Baysari; Wu Yi Zheng; Regis Beuscart (BMJ Open)
Introduction Research has shown that improvements to the usability of medication alert systems are needed. For designers and decisions-makers to assess usability of their alert systems, two paper-based tools are currently available: the instrument for evaluating human-factors principles in medication-related decision support alerts (I-MeDeSA) and the tool for evaluating medication alerting systems (TEMAS). This study aims to compare the validity, usability and usefulness of both tools to identify their strengths and limitations and assist designers and decision-makers in making an informed decision about which tool is most suitable for assessing their current or prospective system.Methods and analysis First, TEMAS and I-MeDeSA will be translated into French. This translation will be validated by three experts in human factors. Then, in 12 French hospitals with a medication alert system in place, staff with expertise in the system will evaluate their alert system using the two tools successively. After the use of each tool, participants will be asked to fill in the System Usability Scale (SUS) and complete a survey on the understandability and perceived usefulness of each tool. Following the completion of both assessments, participants will be asked to nominate their preferred tool and relay their opinions on the tools. The design philosophy of TEMAS and I-MeDeSA differs on the calculation of a score, impacting the way the comparison between the tools can be performed. Convergent validity will be evaluated by matching the items of the two tools with respect to the usability dimensions they assess. SUS scores and answers to the survey will be statistically compared for I-MeDeSA and TEMAS to identify differences. Free-text responses in surveys will be analysed using an inductive approach.Ethics and dissemination Ethical approval is not required in France for a study of this nature. The results will be published in a peer-reviewed journal.